What is a factorial trial? - Cipriani, A; Barbui, C (2013)
Randomized controlled trials (RCTs), typically, randomize participants to one of two intervention groups. It has been shown, however, that about 25% of RCTs published in the scientific literature randomize participants to three or more treatment groups. These studies are called 'multi-arm' trials: there may be, for instance, two or more experimental intervention groups with a common control group, or two control intervention groups such as a placebo group and a standard treatment group. A special case of multi-arm studies are factorial trials, which address two or more intervention comparisons carried out simultaneously, using four or more intervention groups.